ORGANIZATION OF TRAINING OF PARTICIPANTS OF OLYMPIAD IN INFORMATICS BY FACILITIES OF INTERNET-PORTAL E-OLIMP - Zhukovskiy, C.C. (Journal of Information Technologies in Education (ITE), 2010)
In the article the organizational section of Internet-portal of organizationally methodical providing of preparation of distance olympiads in programming for the endowed young people of educational establishments of Ukraine is described. The methodology of training of students to the olympiad in programming by facilities of Internet-portal E-OLIMP is developed.